Animating the critical zone: beavers as critical zone engineers - Adamchak, Clifford; Lininger, Katherine B.; Hinckley, Eve-Lyn S. (Frontiers in Water, 2025)
Beavers (Castor canadensis) have not been adequately included in critical zone research, yet they can affect multiple critical zone processes across the terrestrial-aquatic interface of river corridors. River corridors (RC) provide a disproportionate amount of ecosystem services. Over time, beaver activity, including submersion of woody vegetation, burrowing, dam building, and abandonment, can impact critical zone processes in the river corridor by influencing landscape evolution, biodiversity, geomorphology, hydrology, primary productivity, and biogeochemical cycling. In particular, they can effectively restore degraded riparian areas and improve water quality and quantity, causing implications for many important ecosystem services. Beaver-mediated river corridor processes in the context of a changing climate require investigation to determine how both river corridor function and critical zone processes will shift in the future. Recent calls to advance river corridor research by leveraging a critical zone perspective can be strengthened through the explicit incorporation of animals, such as beavers, into research projects over space and time. This article illustrates how beavers modify the critical zone across different spatiotemporal scales, presents research opportunities to elucidate the role of beavers in influencing Western U.S. ecosystems, and, more broadly, demonstrates the importance of integrating animals into critical zone science.